Contributive Analysis Of The Use Of Digital Infographic Media On The Chronological Thinking Ability Of SMK Students - Heri Susanto; Kamelia Amiruddin; Fathurrahman Fathurrahman; Sriwati Sriwati; Siswandari Siswandari; Helmi Akmal (Wahana Pendidikan, 2025)
The difficulty vocational students have in understanding the chronology of historical events is the background of this study. The purpose of the study was to analyze the effect of digital infographic media on the chronological thinking ability of students in class XI MPLB at SMK Negeri 1 Banjarmasin. The research method used a quantitative experimental approach with a true experimental post-test-only control design. This study involved 48 students who were divided into experimental and control groups. Data collection was done through cognitive tests and documentation, with data analysis using a t-test. The results showed that the use of digital infographic media had a significant effect on students' chronological thinking ability, where the experimental class showed better ability than the control class. Digital infographic media proved to be effective in helping students understand the chronology of historical events, improve understanding of cause-and-effect relationships, and increase interest and motivation to learn. This research has implications for the importance of integrating digital technology in history learning and developing students' chronological thinking skills in a temporal context.